CORRELATION BETWEEN ONLINE LEARNING DURING PANDEMI COVID-19 TO SENIOR HIGH SCHOOL STUDENTS MOTIVATION IN LEARNING CHEMISTRY IN KENDARI - Aminuddin, Aminuddin; Nurlansi, Nurlansi; Rahman, Abraham (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2022)
The aims of this study is to ivestigate the correlation between online learning during the Covid-19 pandemic and the motivation to study chemistry for Class XIth grade of senior high school students in Kendari City. This research is a quantitative descriptive research using survey method. The population of the study were teachers and students in XIth grade of scieneinÂ Kendari City with 17 teachers and 2266 students. The sample used purposive sampling technique with a sample of 325 students, while the teacher sample was the entire population. The data used are questionnaires (questionnaires), observations, and structured interviews. Data were analyzed descriptively and inferentially. The results showed that the online learning process was running quite well in the medium category with an average value of 71.21, and the average value of learning motivation of 71.12 belonging to the medium category. The results of a simple correlation test show that online learning with learning motivation gets a correlation coefficient value of 0.148 which indicates that there is a positive and significant relationship between online learning during the covid-19 pandemic on learning motivation and learning achievement of XIÂ grade of senior high school students in Kendari City.